Implementasi Manajemen Humas Dalam Meningkatkan Kepercayaan Masyarakat Lingkungan Sekolah Di SMKS NU Kota Tasikmalaya - MAYASARI, EMA; Halimah, Ai Hilyatul; Murtado, Dodo (Institut Nahdlatul Ulama Tasikmalaya, 2024)
Public relations management is very important in realizing a quality school. However, public relations management often goes unnoticed in educational institutions. When there is a good relationship between the school and the community, there will be harmonization between the two. The community will trust the school so that they send their children to these institutions and the school can maintain its existence. The aims of this study were: (1) to determine public relations management at NU SMKS Tasikmalaya City, (2) to determine the level of public trust in the school environment at NU SMKS Tasikmalaya City, and (3) to determine the implementation of public relations management in increasing public trust in the school environment in NU SMKS Tasikmalaya City. The thinking framework of this research is public relations management activities with indicators consisting of publicity, marketing, public affairs, issues management, lobbying, and investor relations. While the strategy for building community trust in the school environment with indicators consists of the desires, needs and expectations of the community. The method in this research is through the level of descriptive explanation using the case study method. The approach uses a qualitative approach. The data collection technique for this research was by means of observation, interviews and documentation and the data were analyzed through data reduction, data presentation and drawing conclusions. The results showed (1) on public relations management at NU SMKS Tasikmalaya City based on public relations management indicators, namely publicity,public affairs, issues management, lobbying, and investor relations . Judging from the results of observations, interviews and documentation in the field, it shows that the management of public relations at the Tasikmalaya City NU Vocational High School as a whole has been going well even though it is not optimal. (2) The level of public trust in the school environment at NU SMKS Tasikmalaya City is based on indicators on the desires, needs and expectations of the community. What are the wishes, needs and expectations of the community for the school, the school always adjusts so that both sides give each other Feedback positive for the advancement of education. (3) The implementation of public relations management in increasing the trust of the school environment community at the Tasikmalaya City NU Vocational High School, shows that the implementation of public relations management at the Tasikmalaya City NU Vocational High School has been going well so that the environmental community's trust in the school has increased as seen from the graph of the ups and downs of new students from year to year.